Enterprise Skills and Firm Performance in Zambia : Evidence from Structural Equation Modeling of a Skills Demand Model - World Bank (World Bank, Washington, DC, 2018)
The objective of this Note is to investigate the skills that formal sector Zambian firms demand, the skill deficits they face, the strategies that firms may use to mitigate skill deficits, and their impacts on firm performance. The Note addressed these issues by estimating a multi-equation skills demand model, using Structural Equation Modeling (SEM) methods, on unique data of 350 formal sector firms developed and fielded jointly with the Enterprise Survey Unit of the Development Economics Vice Presidency (DEC). The skills demand model related several latent constructs—organizational capital that drives skills demand, skill gaps as perceived by employers, and skill strategies—to firm-level productivity and wage outcomes. The findings are consistent with the predictions of the new productivity literature, skill-biased technological change, and research on education and training. First, ostensibly similar firms of the same size within the same sector can have very different skill needs and skill strategies that affect firm performance. The firm’s organizational capital (know-how) drives skills demand which, in the short term, is manifested in skill deficits and in firm strategies to mitigate skill gaps and respond to demand. High-skills demand firms, such as those that innovate or export, face greater deficiencies in workers’ cognitive and non-cognitive skills that pose operational constraints for use of technology, innovation, quality, and production. Some firms, but not others, respond with skill strategies to fill job vacancies, hire skilled expatriates, provide in-service training, and outsource professional services. They also employ a more skilled workforce with a higher share of tertiary-educated and TEVET-credentialed workers, and workers in management, professional, and technician occupations. Second, production function estimates revealed that skill deficits negatively affect labor productivity while responsive skill strategies improve productivity outcomes. Interestingly, organization capital only affects productivity through its effect on increasing skills demand and thus expanding the gap between desired and available skills and on eliciting skill strategies from some firms but not others to address these skills gaps. The endogenous choice to deploy skill strategies was addressed using an instrumental variable measuring the density of access to skill sources for firms located in different regions and sectors. Instrumenting for skill strategies increased our estimates of the causal impact of skill strategies on labor productivity. Finally, improvements in labor productivity are associated with higher firm-level wages. In wage equations controlling for skills composition of the workforce, industry and location, firms with higher labor productivity paid significantly higher average wages, roughly equivalent to two-thirds of the higher labor productivity. Like the production function results, skill gaps are associated with lower average wages while skill strategies improve wage outcomes. This result is consistent with the hypothesis that high skills-demanding firms and firms investing in the skills of their current workforce pay wage premiums to attract, reward, and retain their most skilled workers. Wage levels are lower on average in manufacturing relative to service sectors, and in Lusaka-based firms, as compared to firms outside Lusaka which face greater skill shortages.